Determinants of Capital Structure: A Case of Nepalese Non-Financial Firms - Kandel, Amrit; Karki, Aashiyana; KC, Astha; Dahal, Ayush (Nepalese Journal of Economics, 2024)
This study examines the determinants of capital structure in the context of Nepalese non-financial firms. Short term debt ratio and long term debt ratio are selected as the dependent variables. The selected independent variables are assets tangibility, liquidity, non-debt tax shields, firm size, profitability, Tobin’s q and firm’s age. The study is based on secondary data with 105 observations from 7 hydro power firms, 3 hotel industries and 4 manufacturing firms listed in Nepal Stock Exchange (NEPSE). The data were collected from annual reports of the selected non-financial firms. The correlation coefficients and regression models are estimated to test the significance and importance of determinants of capital structure in the context of Nepalese non-financial firms.The study showed that assets tangibility has a positive impact on long-term debt ratio and short-term debt ratio. It indicates that higher the assets tangibility, higher would be the long-term debt ratio and short-term debt ratio. Similarly, liquidity has a positive impact on long-term debt ratio and short-term debt ratio. It indicates that increase in liquidity leads to increase in long-term debt ratio and short-term debt ratio. Likewise, non-debt tax shields has a positive impact on long-term debt ratio and short-term debt ratio. It indicates that increase in non-debt tax shields leads to increase in long-term debt ratio and short-term debt ratio. Further, firm size has a positive impact on long-term debt ratio and short-term debt ratio. It indicates that increase in firm size leads to increase in long-term debt ratio and short-term debt ratio. In addition, profitability has a positive impact on long-term debt ratio and short-term debt ratio. It indicates that increase in profitability leads to increase in long-term debt ratio and short-term debt ratio. Likewise, Tobin’s q has a positive impact on long-term debt ratio and short-term debt ratio. It indicates that higher the Tobin’s q, higher would be the long-term debt ratio and short-term debt ratio. Moreover, firm’s age has a negative impact on long-term debt ratio and short-term debt ratio. It indicates that higher the firm’s age, higher would be the long-term debt ratio and short-term debt ratio.